Preparation method of W-Cu component continuous gradient structure contact and contact

Through the three-screw two-component single nozzle 3D printer and mixer mixer mixing technology, W-Cu component continuous gradient structure contacts were prepared, which solved the matching problems of arc ablation and conduction performance of existing high-pressure contact materials under high energy density and high-temperature gas arc extinguishing conditions, and achieved higher arc ablation and overall conduction performance.

CN119663034AActive Publication Date: 2025-03-21XIAN UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510100350.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-21
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

In the face of high-voltage contact materials with high energy density and high-temperature gas arc extinguishing conditions, it is difficult to simultaneously improve arc ablation resistance and overall conduction performance. The functional gradient materials are discontinuous gradient structures, and there are problems of component differences and interlayer interface thermal stress.

Method used

A three-screw two-component single nozzle 3D printer is used to mix W powder and Cu powder with binder through a mixer to realize the preparation of W-Cu component continuous gradient structure composite material, including solvent degreasing, thermal degreasing and sintering, forming W-Cu contacts with continuous gradient structure.

Benefits of technology

The W-Cu component continuous gradient structure contacts are prepared, and the arc ablation resistance at the surface arc end is improved by using high W content, while avoiding thermal stress between the interlayer interfaces, ensuring that the overall conduction performance is not reduced, and the reasonable matching of the arc ablation resistance at the surface arc end and the overall conduction performance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663034A_ABST
    Figure CN119663034A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a W-Cu component continuous gradient structure contact and the contact, and the specific process is as follows: step 1, mixing W powder with a binder by using an internal mixer to obtain a feed A, and mixing Cu powder with the binder by using the internal mixer to obtain a feed B; 2, the feed A and the feed B are mixed, printed and extruded through a three-screw two-component single-nozzle 3D printer, and a W-Cu component continuous gradient structure composite material green body is obtained; 3, solvent degreasing, drying and thermal degreasing are conducted on the W-Cu component continuous gradient structure composite material green body, and a degreased blank of the W-Cu component continuous gradient structure composite material is obtained; step 4, sintering the degreased blank of the W-Cu component continuous gradient structure composite material to obtain the W-Cu component continuous gradient structure composite material; and 5, machining the W-Cu component continuous gradient structure composite material to obtain the W-Cu component continuous gradient structure contact. Components of the W phase and the Cu phase in the contact obtained through the method change in a continuous gradient mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric contact preparation, and in particular relates to a method for preparing a W-Cu component continuous gradient structure contact, and also relates to a W-Cu component continuous gradient structure contact. Background Art

[0002] With the urgent need to improve power generation efficiency, the unit capacity of nuclear power, hydropower and other generating units in my country will continue to increase, requiring the rated short-circuit breaking current of the generator circuit breaker to exceed 250kA, or even reach 300kA. As the breaking current increases from 190kA to 250kA, the energy density of the contacts, the core components responsible for connecting and disconnecting in the circuit breaker, will increase by nearly one-fold, posing an unprecedented test on its arc erosion resistance. At the same time, the arc extinguishing medium SF6 gas commonly used in high-voltage circuit breakers has a greenhouse effect 23,900 times that of CO2, and will be gradually replaced in the future. Perfluoroisobutyronitrile (C4F7N, referred to as C4) stands out in its arc extinguishing characteristics among many environmentally friendly gases that replace SF6, but its arc extinguishing ability is still more than 50% lower than that of SF6, and the requirements for the contact erosion resistance have also more than doubled accordingly. Under this dual pressure, it is urgent to significantly improve the arc erosion resistance of existing contact materials.

[0003] At present, the widely used high-voltage contacts are made of ablation-resistant tungsten-copper (W-Cu) alloy with high melting point, high strength and excellent resistance to welding, and conductive copper (Cu) alloy with good conductivity. The ablation performance of W-Cu alloy is closely related to conventional properties such as conductivity and skeleton strength. For example, the improvement of ablation performance often leads to a decrease in conductivity, which in turn affects the ability to resist arc ablation. Therefore, this mutually restrictive relationship makes the improvement of arc ablation resistance challenging. The functional gradient structure is an effective way to achieve the mutual matching of local performance optimization and overall performance of the material, but the functional gradient material currently used is a layered non-continuous gradient structure, and there are still composition differences between its layers. The interlayer interface thermal stress caused by the composition difference will greatly reduce the service life of the material. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a W-Cu component continuous gradient structure contact, so as to solve the problem that the functional gradient material used to prepare the existing contact has a discontinuous gradient structure and has component differences.

[0005] Another object of the present invention is to provide a W-Cu continuous gradient structure contact obtained by the above preparation method.

[0006] The technical solution adopted by the present invention is a method for preparing a W-Cu component continuous gradient structure contact, which is specifically implemented according to the following steps: Step 1, using an internal mixer to mix W powder and a binder to obtain feed A, and using an internal mixer to mix Cu powder and a binder to obtain feed B; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu continuous gradient structure composite green body; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; Step 4, sintering the degreased blank of the W-Cu continuous gradient structure composite material in a tubular furnace to obtain a W-Cu continuous gradient structure composite material; Step 5, machining the W-Cu component continuous gradient structure composite material according to design requirements to obtain a W-Cu component continuous gradient structure contact. The present invention is also characterized in that, in step 1, the average particle size of the W powder is 400nm~20μm, and the average particle size of the Cu powder is 400nm~5μm.

[0007] Furthermore, in step 1, the binder is composed of the following components in mass percentage: 40% to 60% microcrystalline wax, 0% to 20% liquid paraffin, 0% to 15% low-density polyethylene, 15% to 39% high-density polyethylene, 0% to 12% ethylene-vinyl acetate copolymer, and 1% stearic acid, and the sum of the mass percentages of the above components is 100%.

[0008] Furthermore, in step 1, the mixing temperature is 130° C. to 170° C., and the mixing time is 2 h to 5 h.

[0009] Furthermore, in step 1, the volume loading rate of the powder in feed A and feed B is 35% to 55%.

[0010] Furthermore, in step 2, the heating temperatures of feed A and feed B are both 130°C to 200°C.

[0011] Furthermore, the specific process of step 3 is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 40°C to 70°C, immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 40h to 90h; Step 3.2, moving the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 to immerse in kerosene, taking it out after immersion and naturally air-drying it for 2h~6h, and placing the W-Cu continuous gradient structure composite material green body in an oven for drying after air-drying; Step 3.3, placing the W-Cu continuous gradient structure composite material green body dried in step 3.2 in a tubular furnace for thermal debinding to obtain a W-Cu continuous gradient structure composite material debinding body.

[0012] Furthermore, in step 3.2, the drying temperature is 40°C~80°C, and the drying time is 4h~10h; in step 3.3, the temperature of thermal degreasing is 200°C~700°C, the heating rate is 0.1°C / min~2°C / min, and the holding time is 1h~4h.

[0013] Furthermore, in step 4, the sintering temperature is 1200°C to 1600°C, the holding time is 1h to 4h, and the heating rate is 5°C / min to 15°C / min.

[0014] Another technical solution adopted by the present invention is that the W-Cu component continuous gradient structure contact is obtained by adopting the above-mentioned preparation method.

[0015] The beneficial effects of the present invention are: (1) The W-Cu composition continuous gradient structure contact obtained by the preparation method of the present invention has a composition continuous gradient change between the W phase and the Cu phase, and the arc erosion resistance of the surface arc end can be improved by using a high W content. At the same time, the composition continuous gradient structure can avoid large thermal stress at the interlayer interface and ensure that the overall conductive performance is not reduced, thereby achieving a reasonable match between the arc erosion resistance of the surface arc end of the W-Cu composition continuous gradient structure contact and the overall conductive performance; (2) The preparation method of the W-Cu continuous gradient structure contact of the present invention adopts a three-screw two-component single-nozzle 3D printer to realize a double-input and one-output powder extrusion molding method, which can control the components in the W-Cu continuous gradient structure composite material green body in real time, and thus obtain the W-Cu continuous gradient structure contact. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The schematic diagram of the microstructure of the W-Cu continuous gradient structure contact obtained by the preparation method of the present invention. DETAILED DESCRIPTION

[0017] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0018] The method for preparing the W-Cu component continuous gradient structure contact of the present invention is specifically implemented according to the following steps: Step 1: using an internal mixer to mix W (tungsten) powder with an average particle size of 400nm~20μm with a binder for 2h~5h at a mixing temperature of 130℃~170℃ to obtain feed A; using an internal mixer to mix Cu (copper) powder with an average particle size of 400nm~5μm with a binder for 2h~5h at a mixing temperature of 130℃~170℃ to obtain feed B; The binder is composed of the following components by mass percentage: 40% to 60% microcrystalline wax, 0% to 20% liquid paraffin, 0% to 15% low-density polyethylene, 15% to 39% high-density polyethylene, 0% to 12% ethylene-vinyl acetate copolymer, and 1% stearic acid, and the sum of the mass percentages of the above components is 100%; Among them, microcrystalline wax and liquid paraffin are plasticizing components, low-density polyethylene, high-density polyethylene and ethylene-vinyl acetate copolymer are bonding components, and stearic acid is an activating component; Among them, the volume loading rate of powder in feed A and feed B is 35%~55%; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu continuous gradient structure composite green body; The specific process is as follows: the three-screw two-component single-nozzle 3D printer adopts the method of double-sided feeding and intermediate mixing extrusion for printing and extrusion. Feed A is added to one of the silos and melted and extruded, and feed B is added to the other silo and melted and extruded. The molten feed A and feed B extruded from the two silos are mixed in the mixing silo and then printed and extruded. The heating temperature required for melting feed A and feed B is 130℃~200℃, and the W-Cu component continuous gradient structure composite green body is obtained; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; The specific process is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 40°C to 70°C, immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 40h to 90h; The height of n-heptane covering the W-Cu continuous gradient structure composite material green body is not less than 5 cm; Step 3.2, transferring the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 to kerosene for immersion for 30 minutes, taking it out and naturally air-drying it for 2 hours to 6 hours after the immersion, and placing the W-Cu continuous gradient structure composite material green body in an oven at a temperature of 40° C. to 80° C. for 4 hours to 10 hours after air-drying; Among them, the height of the W-Cu component continuous gradient structure composite material green body after kerosene solvent degreasing is not less than 5cm; Step 3.3, placing the W-Cu continuous gradient structure composite material dried in step 3.2 in a tubular furnace and performing thermal debinding at a temperature of 200°C to 700°C for 1h to 4h at a heating rate of 0.1°C / min to 2°C / min to obtain a debinded blank of the W-Cu continuous gradient structure composite material; Step 4, sintering the debinded blank of the W-Cu continuous gradient structure composite material in a tube furnace at a heating rate of 5°C / min-15°C / min at a temperature of 1200°C-1600°C for 1h-4h to obtain a W-Cu continuous gradient structure composite material; Step 5, machining the W-Cu component continuous gradient structure composite material according to design requirements to obtain a W-Cu component continuous gradient structure contact.

[0019] The W-Cu component continuous gradient structure contact of the present invention is obtained by adopting the preparation method of the W-Cu component continuous gradient structure contact.

[0020] The preparation method of the W-Cu component continuous gradient structure contact of the present invention changes the bonding force between powder particles by a binder so that the powder particles are more evenly distributed, and adopts a three-screw two-component single-nozzle 3D printer to realize two-component variable gradient extrusion molding printing, and obtains a W-Cu component continuous gradient structure contact with a certain strength after degreasing and sintering. The component continuous gradient structure can improve the interface bonding strength between the W phase and the Cu phase, improve the mechanical properties of the contact, and do not reduce its overall conductivity while meeting the arc ablation resistance performance; at the same time, the three-screw two-component single-nozzle 3D printer printing molding technology adopted by the present invention has the advantages of low-temperature molding and high-temperature forming, and can solve the problem that refractory metal W and high thermal conductivity and high reflectivity metal Cu are difficult to directly print and mold, and provides a new method for the controllable preparation of W-Cu component continuous gradient structure contacts.

[0021] Example 1 Step 1: using an internal mixer to mix W powder with an average particle size of 1 μm and a binder at a mixing temperature of 150° C. for 2 hours to obtain feed A; using an internal mixer to mix Cu powder with an average particle size of 5 μm and a binder at a mixing temperature of 150° C. for 2 hours to obtain feed B; The binder is composed of the following components by mass percentage: 50% microcrystalline wax, 10% liquid paraffin, 12% low-density polyethylene, 15% high-density polyethylene, 12% ethylene-vinyl acetate copolymer, and 1% stearic acid; Among them, the volume loading rate of W powder in feed A is 52%, and the volume loading rate of Cu powder in feed B is 48%; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu continuous gradient structure composite green body; The specific process is as follows: the three-screw two-component single-nozzle 3D printer adopts the method of double-sided feeding and intermediate mixing extrusion for printing and extrusion. Feed A is added to one of the silos and melted and extruded, and feed B is added to the other silo and melted and extruded. The molten feed A and feed B extruded from the two silos are mixed in the mixing silo and then printed and extruded. The heating temperature required for melting feed A and feed B is 160°C to obtain a W-Cu component continuous gradient structure composite green body; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; The specific process is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 60° C., immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 40 hours; The height of n-heptane covering the W-Cu continuous gradient structure composite material green body is not less than 5 cm; Step 3.2, transferring the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 to kerosene for immersion for 30 minutes, taking it out and naturally air-drying it for 4 hours after the immersion, and placing the W-Cu continuous gradient structure composite material green body in an oven at 80° C. for drying for 6 hours after air-drying; Among them, the height of the W-Cu component continuous gradient structure composite material green body after kerosene solvent degreasing is not less than 5cm; Step 3.3, placing the W-Cu continuous gradient structure composite material dried in step 3.2 in a tubular furnace and performing thermal debinding at a temperature of 700°C for 2 hours at a heating rate of 2°C / min to obtain a debinded blank of the W-Cu continuous gradient structure composite material; Step 4, sintering the debinded blank of the W-Cu continuous gradient structure composite material in a tube furnace at a temperature of 1500° C. for 2 h at a heating rate of 10° C. / min to obtain a W-Cu continuous gradient structure composite material; Step 5, machining the W-Cu component continuous gradient structure composite material according to design requirements to obtain a W-Cu component continuous gradient structure contact.

[0022] Example 2 Step 1: using an internal mixer to mix W powder with an average particle size of 20 μm and a binder for 4 hours at a mixing temperature of 130° C. to obtain feed A; using an internal mixer to mix Cu powder with an average particle size of 5 μm and a binder for 4 hours at a mixing temperature of 130° C. to obtain feed B; The binder is composed of the following components by mass percentage: 60% microcrystalline wax, 15% low-density polyethylene, 15% high-density polyethylene, 12% ethylene-vinyl acetate copolymer, and 1% stearic acid; Among them, the volume loading rate of W powder in feed A is 49%, and the volume loading rate of Cu powder in feed B is 45%; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu continuous gradient structure composite green body; The specific process is as follows: the three-screw two-component single-nozzle 3D printer adopts the method of double-sided feeding and intermediate mixing extrusion for printing and extrusion. Feed A is added to one of the silos and melted and extruded, and feed B is added to the other silo and melted and extruded. The molten feed A and feed B extruded from the two silos are mixed in the mixing silo and then printed and extruded. The heating temperature required for melting feed A and feed B is 150°C to obtain a W-Cu component continuous gradient structure composite green body; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; The specific process is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 50° C., then immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 60 hours; The height of n-heptane covering the W-Cu continuous gradient structure composite material green body is not less than 5 cm; Step 3.2, moving the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 into kerosene and soaking it for 30 minutes, taking it out and naturally air-drying it for 3 hours after soaking, and after air-drying, placing the W-Cu continuous gradient structure composite material green body in an oven and drying it at 70°C for 7 hours; Among them, the height of the W-Cu component continuous gradient structure composite material green body after kerosene solvent degreasing is not less than 5cm; Step 3.3, placing the W-Cu continuous gradient structure composite material dried in step 3.2 in a tubular furnace at a temperature of 650°C for thermal debinding at a heating rate of 1°C / min for 3 hours to obtain a debinded blank of the W-Cu continuous gradient structure composite material; Step 4, sintering the debinded blank of the W-Cu continuous gradient structure composite material in a tube furnace at a temperature of 1400° C. for 3 h at a heating rate of 10° C. / min to obtain a W-Cu continuous gradient structure composite material; Step 5, machining the W-Cu component continuous gradient structure composite material according to design requirements to obtain a W-Cu component continuous gradient structure contact.

[0023] Example 3 Step 1: using an internal mixer to mix W powder with an average particle size of 1 μm and a binder at a mixing temperature of 130° C. for 4 hours to obtain feed A; using an internal mixer to mix Cu powder with an average particle size of 600 nm and a binder at a mixing temperature of 130° C. for 4 hours to obtain feed B; The binder is composed of the following components by mass percentage: 50% microcrystalline wax, 10% liquid paraffin, 15% low-density polyethylene, 24% high-density polyethylene, 12% ethylene-vinyl acetate copolymer, and 1% stearic acid; Among them, the volume loading rate of W powder in feed A is 55%, and the volume loading rate of Cu powder in feed B is 55%; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu continuous gradient structure composite green body; The specific process is as follows: the three-screw two-component single-nozzle 3D printer adopts the method of double-sided feeding and intermediate mixing extrusion for printing and extrusion. Feed A is added to one of the silos and melted and extruded, and feed B is added to the other silo and melted and extruded. The molten feed A and feed B extruded from the two silos are mixed in the mixing silo and then printed and extruded. The heating temperature required for melting feed A and feed B is 130°C to obtain a W-Cu component continuous gradient structure composite green body; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; The specific process is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 70° C., immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 40 hours; The height of n-heptane covering the W-Cu continuous gradient structure composite material green body is not less than 5 cm; Step 3.2, moving the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 into kerosene and soaking it for 30 minutes, taking it out and naturally air-drying it for 2 hours after soaking, and after air-drying, placing the W-Cu continuous gradient structure composite material green body in an oven and drying it at a temperature of 40° C. for 10 hours; Among them, the height of the W-Cu component continuous gradient structure composite material green body after kerosene solvent degreasing is not less than 5cm; Step 3.3, placing the W-Cu continuous gradient structure composite material dried in step 3.2 in a tubular furnace and performing thermal debinding at a temperature of 200° C. for 4 h at a heating rate of 0.1° C. / min to obtain a debinded blank of the W-Cu continuous gradient structure composite material; Step 4, sintering the debinded blank of the W-Cu continuous gradient structure composite material in a tube furnace at a temperature of 1600° C. for 1 hour at a heating rate of 15° C. / min to obtain a W-Cu continuous gradient structure composite material; Step 5, machining the W-Cu component continuous gradient structure composite material according to design requirements to obtain a W-Cu component continuous gradient structure contact.

[0024] Example 4 Step 1: using an internal mixer to mix W powder with an average particle size of 600 nm and a binder at a mixing temperature of 170° C. for 5 hours to obtain feed A; using an internal mixer to mix Cu powder with an average particle size of 400 nm and a binder at a mixing temperature of 170° C. for 5 hours to obtain feed B; The binder is composed of the following components by mass percentage: 40% microcrystalline wax, 20% liquid paraffin, 12% low-density polyethylene, 15% high-density polyethylene, 12% ethylene-vinyl acetate copolymer, and 1% stearic acid; Among them, the volume loading rate of W powder in feed A is 35%, and the volume loading rate of Cu powder in feed B is 35%; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu continuous gradient structure composite green body; The specific process is as follows: the three-screw two-component single-nozzle 3D printer adopts the method of double-sided feeding and intermediate mixing extrusion for printing and extrusion. Feed A is added to one of the silos and melted and extruded, and feed B is added to the other silo and melted and extruded. The molten feed A and feed B extruded from the two silos are mixed in the mixing silo and then printed and extruded. The heating temperature required for melting feed A and feed B is 200°C, and a W-Cu component continuous gradient structure composite green body is obtained; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; The specific process is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 40° C., then immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 90 hours; The height of n-heptane covering the W-Cu continuous gradient structure composite material green body is not less than 5 cm; Step 3.2, transferring the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 to kerosene for immersion for 30 minutes, taking it out and naturally air-drying it for 6 hours after the immersion, and placing the W-Cu continuous gradient structure composite material green body in an oven at 80° C. for 4 hours after air-drying; Among them, the height of the W-Cu component continuous gradient structure composite material green body after kerosene solvent degreasing is not less than 5cm; Step 3.3, placing the W-Cu continuous gradient structure composite material dried in step 3.2 in a tubular furnace and performing thermal debinding at a temperature of 700°C for 1 hour at a heating rate of 2°C / min to obtain a debinded blank of the W-Cu continuous gradient structure composite material; Step 4, sintering the debinded blank of the W-Cu continuous gradient structure composite material in a tube furnace at a temperature of 1200° C. for 4 hours at a heating rate of 5° C. / min to obtain a W-Cu continuous gradient structure composite material; Step 5, machining the W-Cu component continuous gradient structure composite material according to design requirements to obtain a W-Cu component continuous gradient structure contact.

[0025] Example 5 Step 1: using an internal mixer to mix W powder with an average particle size of 400 nm and a binder at a mixing temperature of 150° C. for 5 hours to obtain feed A; using an internal mixer to mix Cu powder with an average particle size of 400 nm and a binder at a mixing temperature of 150° C. for 5 hours to obtain feed B; The binder is composed of the following components by mass percentage: 50% microcrystalline wax, 10% liquid paraffin, 27% high-density polyethylene, 12% ethylene-vinyl acetate copolymer, and 1% stearic acid; Among them, the volume loading rate of W powder in feed A is 50%, and the volume loading rate of Cu powder in feed B is 45%; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu continuous gradient structure composite green body; The specific process is as follows: the three-screw two-component single-nozzle 3D printer adopts the method of double-sided feeding and intermediate mixing extrusion for printing and extrusion. Feed A is added to one of the silos and melted and extruded, and feed B is added to the other silo and melted and extruded. The molten feed A and feed B extruded from the two silos are mixed in the mixing silo and then printed and extruded. The heating temperature required for melting feed A and feed B is 180°C to obtain a W-Cu component continuous gradient structure composite green body; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; The specific process is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 50° C., then immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 80 hours; The height of n-heptane covering the W-Cu continuous gradient structure composite material green body is not less than 5 cm; Step 3.2, moving the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 into kerosene and soaking it for 30 minutes, taking it out and naturally air-drying it for 3 hours after soaking, and after air-drying, placing the W-Cu continuous gradient structure composite material green body in an oven and drying it at a temperature of 50° C. for 8 hours; Among them, the height of the W-Cu component continuous gradient structure composite material green body after kerosene solvent degreasing is not less than 5cm; Step 3.3, placing the W-Cu continuous gradient structure composite material dried in step 3.2 in a tubular furnace for thermal debinding at a temperature of 600°C for 2 hours at a heating rate of 1.5°C / min to obtain a debinded blank of the W-Cu continuous gradient structure composite material; Step 4, sintering the debinded blank of the W-Cu continuous gradient structure composite material in a tube furnace at a temperature of 1500° C. for 2 h at a heating rate of 8° C. / min to obtain a W-Cu continuous gradient structure composite material; Step 5, machining the W-Cu component continuous gradient structure composite material according to design requirements to obtain a W-Cu component continuous gradient structure contact.

[0026] Example 6 Step 1: using an internal mixer to mix W powder with an average particle size of 400 nm and a binder at a mixing temperature of 130° C. for 5 hours to obtain feed A; using an internal mixer to mix Cu powder with an average particle size of 400 nm and a binder at a mixing temperature of 130° C. for 5 hours to obtain feed B; The binder is composed of the following components by mass percentage: 50% microcrystalline wax, 10% liquid paraffin, 39% high-density polyethylene, and 1% stearic acid; Among them, the volume loading rate of W powder in feed A is 54%, and the volume loading rate of Cu powder in feed B is 50%; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu continuous gradient structure composite green body; The specific process is as follows: the three-screw two-component single-nozzle 3D printer adopts the method of double-sided feeding and intermediate mixing extrusion for printing and extrusion. Feed A is added to one of the silos and melted and extruded, and feed B is added to the other silo and melted and extruded. The molten feed A and feed B extruded from the two silos are mixed in the mixing silo and then printed and extruded. The heating temperature required for melting feed A and feed B is 130°C to obtain a W-Cu component continuous gradient structure composite green body; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; The specific process is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 550° C., then immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 80 hours; The height of n-heptane covering the W-Cu continuous gradient structure composite material green body is not less than 5 cm; Step 3.2, moving the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 into kerosene and soaking it for 30 minutes, taking it out and naturally air-drying it for 3 hours after soaking, and after air-drying, placing the W-Cu continuous gradient structure composite material green body in an oven and drying it at a temperature of 60° C. for 8 hours; Among them, the height of the W-Cu component continuous gradient structure composite material green body after kerosene solvent degreasing is not less than 5cm; Step 3.3, placing the W-Cu continuous gradient structure composite material dried in step 3.2 in a tubular furnace at a temperature of 500°C for thermal debinding for 3 hours at a heating rate of 1.5°C / min to obtain a debinded blank of the W-Cu continuous gradient structure composite material; Step 4, sintering the debinded blank of the W-Cu continuous gradient structure composite material in a tube furnace at a temperature of 1600° C. for 1 hour at a heating rate of 10° C. / min to obtain a W-Cu continuous gradient structure composite material; Step 5, machining the W-Cu component continuous gradient structure composite material according to design requirements to obtain a W-Cu component continuous gradient structure contact.

[0027] like Figure 1 As shown, it can be seen that the composition of the W phase and the Cu phase in the W-Cu continuous gradient structure contact obtained by the preparation method of the present invention changes continuously by gradient.

[0028] Comparative Example: CuW70 contacts, CuW75 contacts and CuW80 contacts were prepared respectively by conventional powder pressing and solution infiltration processes in the art.

[0029] The conductivity of the contact obtained in the comparative example is selected according to the national standard GB / T 8320-2003, and the selected conductivity is used to compare with the conductivity of the embodiment of the present invention; the arc ablation resistance performance of the comparative example and the embodiment of the present invention is reflected by the maximum value of the measured withstand voltage strength; the specific test results are as follows: The arc erosion resistance of the W-Cu continuous gradient structure contact obtained in Examples 1 to 6 of the present invention is ≥4.5×10 7 V / m, and the conductivity is in the range of 22%IACS~57%IACS; among them, the comprehensive performance of Example 1 is the best, and the arc erosion resistance of the arc end, i.e., the position with a higher content of the ablation-resistant phase W phase, can reach 9.4×10 7 V / m, and its conductivity can reach 46.76%IACS. The arc erosion resistance of the CuW70 contact obtained in the comparative example is 4.5×10 7 V / m, the conductivity is 42%IACS; the arc erosion resistance of the CuW75 contact obtained in the comparative example is 5.9×10 7 V / m, the conductivity is 38%IACS; the arc erosion resistance of the CuW80 contact obtained in the comparative example is 7.4×10 7 V / m, conductivity is 34%IACS.

[0030] It can be seen from the above test results that the W-Cu continuous gradient composition structure contact obtained in Example 1 of the present invention has an arc erosion resistance performance improved by 25.3% compared with CuW80 with the highest tungsten phase content in the national standard GB / T 8320-2003, and the W-Cu continuous gradient composition structure contact obtained in Example 1 of the present invention has an electrical conductivity improved by 11.3% compared with CuW70 contact with the best electrical conductivity; in summary, the present invention can improve the arc erosion resistance of the surface arc end by using high W content by designing the continuous gradient changes in the composition of the W phase and the Cu phase, and the continuous gradient composition structure can ensure that the overall conductive performance is not reduced, thereby achieving a reasonable match between the arc erosion resistance of the surface arc end of the W-Cu continuous gradient composition structure contact and the overall conductive performance.

Claims

1. A method for preparing a W-Cu component continuous gradient structure contact, characterized in that: Follow the steps below to implement it: Step 1, using an internal mixer to mix W powder and a binder to obtain feed A, and using an internal mixer to mix Cu powder and a binder to obtain feed B; Step 2, using a three-screw two-component single-nozzle 3D printer to mix and print feed A and feed B to obtain a W-Cu component continuous gradient structure composite green body; Step 3, solvent degreasing the W-Cu continuous gradient structure composite material green body, drying it, and placing it in a tube furnace for thermal degreasing to obtain a W-Cu continuous gradient structure composite material degreasing green body; Step 4, sintering the degreased blank of the W-Cu continuous gradient structure composite material in a tubular furnace to obtain a W-Cu continuous gradient structure composite material; Step 5: machining the W-Cu continuous gradient structure composite material according to design requirements to obtain a W-Cu continuous gradient structure contact.

2. The method for preparing a W-Cu continuous gradient structure contact according to claim 1, characterized in that: In step 1, the average particle size of the W powder is 400nm~20μm, and the average particle size of the Cu powder is 400nm~5μm.

3. The method for preparing a W-Cu continuous gradient structure contact according to claim 1, characterized in that: In step 1, the binder is composed of the following components in mass percentage: 40% to 60% microcrystalline wax, 0% to 20% liquid paraffin, 0% to 15% low-density polyethylene, 15% to 39% high-density polyethylene, 0% to 12% ethylene-vinyl acetate copolymer, and 1% stearic acid, and the sum of the mass percentages of the above components is 100%.

4. The method for preparing a W-Cu continuous gradient structure contact according to claim 1, characterized in that: In step 1, the mixing temperature is 130°C to 170°C, and the mixing time is 2h to 5h.

5. The method for preparing a W-Cu continuous gradient structure contact according to claim 1, characterized in that: In step 1, the volume loading rate of powder in feed A and feed B is 35% to 55%.

6. The method for preparing a W-Cu continuous gradient structure contact according to claim 1, characterized in that: In step 2, the heating temperature of feed A and feed B is 130°C to 200°C.

7. The method for preparing a W-Cu continuous gradient structure contact according to claim 1, characterized in that: The specific process of step 3 is: Step 3.1, adding n-heptane into a container and placing it in a water bath and heating it to 40°C to 70°C, immersing the W-Cu component continuous gradient structure composite green body into the n-heptane for solvent degreasing for 40h to 90h; Step 3.2, transferring the W-Cu continuous gradient structure composite material green body after solvent degreasing in step 3.1 to kerosene for immersion, taking it out after immersion and naturally air-drying it for 2h~6h, and placing the W-Cu continuous gradient structure composite material in an oven for drying after air-drying; Step 3.3, placing the W-Cu continuous gradient structure composite material green body dried in step 3.2 in a tubular furnace for thermal debinding to obtain a W-Cu continuous gradient structure composite material debinding body.

8. The method for preparing a W-Cu continuous gradient structure contact according to claim 7, characterized in that: In step 3.2, the drying temperature is 40°C to 80°C, and the drying time is 4h to 10h; In step 3.3, the temperature of thermal degreasing is 200°C~700°C, the heating rate is 0.1°C / min~2°C / min, and the holding time is 1h~4h.

9. The method for preparing a W-Cu continuous gradient structure contact according to claim 1, characterized in that: In step 4, the sintering temperature is 1200°C~1600°C, the holding time is 1h~4h, and the heating rate is 5°C / min~15°C / min.

10. W-Cu composition continuous gradient structure contact, characterized in that: The method is adopted as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • 3D printing method for preparing multi--region composite material

    CN111203541A

  • Preparation method of W-Cu functionally graded material and corresponding material

    CN116275090A

  • Preparation method of complex-interface polycrystalline diamond compact based on powder extrusion printing molding

    CN116493601A

  • Gradient structure hard alloy additive manufacturing method

    CN117282978A

  • Polycrystalline diamond compact with continuous gradient transition layer and 3D printing preparation method thereof

    CN117464010A